Minimally Invasive Gastric Electrical Stimulation Using a Newly Developed Wireless Gastrostimulator: A Pilot Animal Study - Kim, Seung Han (J Neurogastroenterol Motil, 2020)
BACKGROUND/AIMS: Gastric electrical stimulation (GES) is a feasible modality for the treatment of gastroparesis; however, the presently available device requires invasive surgical implantation for long-term stimulation and repeated surgical procedure after a period of time. This study is aimed at developing a wireless miniature GES device and testing its endoscopic insertion in animal models. METHODS: Endoscopic gastric implantation of the GES device was performed on 5 healthy weaner pigs under general anesthesia. We created an endoscopic submucosal pocket and inserted the gastro-electrical stimulator. In vivo gastric slow waves were recorded and measured during electrical stimulation. A multi-channel recorder, called an electrogastrogram, was used to record the gastric myoelectrical activity in the study. RESULTS: The gastric slow waves on the electrogastrogram were more consistent with GES on the gastric tissues compared to no stimulation. The frequency-to-amplitude ratio was also significantly altered after the electrical stimulation. CONCLUSIONS: GES is feasible with our minimally invasive wireless device. This technique has the potential to increase utilization of GES as a treatment alternative.